2012
DOI: 10.1007/s12328-012-0343-0
|View full text |Cite
|
Sign up to set email alerts
|

Giant cavernous hepatic hemangioma shrunk by use of sorafenib

Abstract: Here we report a case of a 76-year-old man with a giant cavernous hepatic hemangioma of more than 20 cm in diameter. Since the hepatic hemangioma was actually growing and might possibly rupture and he complained of abdominal symptoms, we decided to perform interventional therapy. First we performed transcatheter arterial embolization (TAE) of the hepatic arteries. However, since this was not sufficiently effective, we added sorafenib (600 mg/day). As a result, the tumor shrank with symptomatic improvement. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Recently, it has been shown that an increase in vascular endothelial growth factor (VEGF) plays an essential role in the development of hemangioma [16]. This concept was supported by case reports showing hemangioma shrinkage following anti-VEGF treatment [17]. However, Lee et al [18] found no effect in 21 anti-VEGF-treated patients.…”
Section: Hemangiomamentioning
confidence: 98%
“…Recently, it has been shown that an increase in vascular endothelial growth factor (VEGF) plays an essential role in the development of hemangioma [16]. This concept was supported by case reports showing hemangioma shrinkage following anti-VEGF treatment [17]. However, Lee et al [18] found no effect in 21 anti-VEGF-treated patients.…”
Section: Hemangiomamentioning
confidence: 98%
“…9 Transcatheter arterial embolization of the hepatic arteries has been adopted for tumor shrinkage, with or without the association of sorafenib administration. 10 Transcatheter arterial embolization has also been proposed for the sequential management of ruptured, bleeding liver tumors and for nonsurgical treatment of symptomatic giant liver hemangiomas. 9,11 Conversely, very recently, a study by Kneuertz et al 2 analyzed which factors most impacted quality of life to determine which patients derived the most benefit from surgery for benign liver lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplantation is an option for treating giant hemangioma for which surgical resection is impossible [19] . In a recent report, a hemangioma was shrunk using monoclonal antibodies such as bevacizumab [14] or sorafenib [20] . While the pathophysiology of hemangioma is not clearly defined, it is known that abnormal vasculogenesis and angiogenesis may be involved [21] .…”
Section: A B C Dmentioning
confidence: 99%